Effect of Personal Protective Equipment during Pesticide Application to Neurological Symptoms in Farmers in Purworejo District, Indonesia - Nurcandra, Fajaria; Mahkota, Renti; Shivalli, Siddharudha (Kesmas, 2018)
Agriculture is one of major sectors of Indonesia economic source with the high volume of pesticide used. Unfortunately, adverse health effect of neurotoxic pesticide has never been reported in Indonesia. This study aimed to determine effectiveness of personal protective equipment (PPE) during applied pesticides to neurological symptoms in farmers. This study was cross-sectionally conducted from April to May 2016 in Purworejo District. About 125 farmers were selected using purposive sampling, and restriction was applied in male farmers due to the high proportion of male sprayer. Data was collected by observation and interview. Logistic regression showed protective result of PPE used during preparing (POR=0.402; 95% CI 0.114-1.423) and spraying (POR = 0.382; 95% CI 0.110-1.320), also following wind direction (POR = 0.882; 95% CI 0.271-2.872) and bathing after spraying (POR=0.328; 95% CI 0.036-3.006) after controlled by confounders. Proper PPE used during preparing and spraying pesticide, following wind direction during spraying, and bathing after spraying can decrease risk of neurological symptoms because of pesticide exposure.